Innocence unveiled: the systemic, social and structural factors behind wrongful convictions in Australia - Ruyters, Michele (Palgrave Macmillan, 2025)
The book examines the unique dynamics surrounding wrongful convictions, particularly in Australia. Transcending the established understanding of wrongful conviction that emerged from the US innocence movement, the book provides a holistic insight into errors in the Australian justice and legal systems that lead to acknowledged and legally unacknowledged errors. Built upon the experiences of the country’s innocence projects, the book moves beyond the established causal factors recognized in the international experience of wrongful conviction to highlight structural and systemic elements that contribute to miscarriages of justice around the world. By offering a global perspective on the struggles of the wrongfully convicted, the book provides a nuanced discussion of why the innocent are convicted of crimes they did not commit and why overturning these errors is increasingly complex and difficult, and more so outside of America. It also presents the risk of wrongful conviction from the perspective of innocence project practitioners who work with cases that can progress through appeal structures and those that unfortunately do not meet the requirements despite evidence of their client’s innocence. Overall, the book expands discussions of what factors contribute to wrongful conviction to support more advocacy, research, and policy reform across legal and justice systems. Michele Ruyters is Professor and Associate Dean of Criminology and Justice Studies at RMIT University, Australia. She is the Founder and Director of the Bridge of Hope Innocence Initiative and the Bridge of Hope Criminal Case Review Project and leads all case investigations. Greg Stratton is Senior Lecturer in Justice and Legal Studies at RMIT University and is also the co-founder and Manager of The Bridge of Hope Innocence Initiative at RMIT University, Australia. Alyssa Sigamony is Lecturer in Criminology and Justice Studies at RMIT University, Australia, and Assistant Manager of the Bridge of Hope Innocence Initiative. Monique Moffa is Lecturer in Criminology and Justice Studies at RMIT University, Australia, and Assistant Manager of the Bridge of Hope Innocence Initiative. Jarryd Bartle is Lecturer in Criminology and Justice Studies at RMIT University, Australia, and a consultant for the Bridge of Hope Innocence Initiative.